"Distance Learning in the age of Social Distancing: Critical Perspectives from Indian Higher Education" (Comparative & International Education Series, 2021)
Distance learning has a long history. The first recorded history of distance learning can be traced to an advertisement for private correspondence courses in shorthand in the Boston Gazette in the year 1728. But, recently distance learning has become the only possible solution to continue teaching and learning, as 1.5 billion students around the world are out of schools and colleges because of the COVID-19 related lockdowns, according to UNESCO (April 2020). But, how are teachers and students adapting to this sudden need for mainstreaming distance education? This chapter will present auto-ethnographic account of faculty and students from a higher educational institution in India engaged in online teaching and learning in the context of COVID-19. The chapter will situate the contextual discussion within the larger body of research literature on distance learning and, education as a social process. It will discuss how distance learning evolved to expand access to higher education and the problems of mainstream Indian higher education. Finally, the chapter will conclude on how COVID-19 related lockdown is re-shaping distance learning in the age of social distancing, as revealed from the auto-ethnographic accounts of students and faculty within a higher education space in India.